Intermittent Preventive Treatment of Malaria in Pregnancy with Sulphadoxine-Pyrimethamine and its Associated Factors in the Atwima Kwanwoma District, Ghana - Emmanuel Kumah; Ferguson Duvor; Godfred Otchere; Samuel Egyakwa Ankomah; Adam Fusheini; Collins Kokuro; Akua Kusiwaa Karikari; Joseph Adom (Ubiquity Press, 2022)
Background: Intermittent preventive treatment of malaria in pregnancy with Sulphadoxine-Pyrimethamine (IPTp-SP) tablets is one of the recommended interventions to reduce the burden of malaria on both the pregnant woman and the unborn child. The aim of this study was to assess the prevalence of IPTp-SP uptake and its associated factors in the Atwima Kwanwoma District of Ashanti Region, Ghana. Methods: The study was cross sectional. A structured questionnaire was administered to 394 respondents, comprising pregnant women in their last two months of pregnancy and nursing mothers who delivered within three months prior to the study. Medical records of the respondents were also reviewed. Descriptive statistics such as simple proportions, and averages were computed. Chi-square test and multiple logistic regression analysis were performed to determine factors associated with IPTp-SP uptake. Results: The average age of the respondents was 28.2 (±5.9) years. Almost all of the respondents (98%) had received SP at the time of the study. Fifty percent received their first dose of SP between 16 and 19 weeks of gestation. The multiple logistic regression analysis showed a statistically significant association between IPTp-SP uptake and educational level, time of first ANC visit, number of ANC visits and receiving education on SP prior to the administration of the drug. Conclusion: Education on SP use should be intensified at all levels of the health system. Early initiation of ANC is also recommended for optimal uptake of IPTp-SP. More research is needed to understand factors affecting the uptake of SP during pregnancy in the country.